An adolescent with primary cutaneous follicle center lymphoma: a case report and literature review - Niu, Wen-Yan; Yan, Xue-Shen; Qiao, Han; Sun, Yu-Jiao; Gu, Hai-Yan; Li, Guang-Lun; Cui, Zhong-Guang; Du, Juan (Frontiers in Oncology, 2023)
Primary cutaneous follicle center lymphoma (PCFCL) differs from follicular lymphoma in biological behavior and molecular profile and is treated as a distinct entity, according to the 5th edition of the World Health Organization classification of hematolymphoid tumors. It is an uncommon cutaneous B-cell lymphoma that is considerably rare in children and adolescents. To date, only 13 cases of individuals younger than 20 years of age have been reported in the literature. The lack of relevant clinical epidemiological data in this population has hampered the investigation of its clinical and diagnostic aspects. Here, we report the case of a 17-year-old male with PCFCL, which may be the first PCFCL patient under 20 years of age reported in China. He was admitted to the hospital with a solitary nodule on his face. After complete surgical excision, the patient's facial mass was histologically identified as PCFCL. The patient's prognosis was favorable, with no recurrence at 17 months of follow-up after surgical resection. We present a case of an adolescent PCFCL patient and systematically review the literature with a view to increasing awareness of the disease and informing the diagnosis and treatment of this age group.